Benchmarking - Christopher P. Chambers; Alan D. Miller (Theoretical Economics, 2018)
We investigate a normative theory of incomplete preferences in the context of preliminary screening procedures. We introduce a theory of ranking in the presence of objectively incomparable marginal contributions (apples and oranges). Our theory recommends benchmarking, a method under which an individual is deemed more accomplished than another if and only if she has achieved more benchmarks, or important accomplishments. We show that benchmark rules are characterized by four axioms: transitivity, monotonicity, incomparability of marginal gains, and incomparability of marginal losses.
Keywords: A10; C71; D63; 330; Benchmarking; axioms; measurement; apples and oranges; incompleteness; closure operator; homomorphisms